PENGARUH SIKAP KERJA, KEADILAN DISTRIBUTIF DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN DI YAYASAN PONDOK PESANTREN ROUDLOTUT THOLIBIN BALEN - jurnalmap map; Khabibur Rochman; Woro Utari; Cathrine Sri Hartati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2019)
ABSTRACT The purpose of this study is to study and describe work conditions, distributive justice, organizational commitment and employee satisfaction, analyze work attitudes, distributive justice and organizational commitment related simultaneously to the significance of employee satisfaction, and improve work relations, distribution, and organizational commitment with partial significant effect on employee satisfaction at the Roudlotut Tholibin Balen Islamic Boarding School Foundation in Bojonegoro Regency. This type of research is quantitative explanatory research. The population in this study were all teachers at the Roudlotut Tholibin Balen Islamic Boarding School Foundation in Bojonegoro Regency who received 35 people. The results of the study show partially the variables of work attitude, distributive justice and organizational commitment have a significant effect on employee job satisfaction. Simultaneously work attitudes, distributive justice and significant organizational commitment to employee job satisfaction. Keywords: work attitude, distributive justice, organizational commitment, job satisfaction